Emotional Intelligence and Leadership Effectiveness: Evidence from Nepalese Commercial Banks - Hamal, Janga Bahadur; Pokharel, Ayushma; Singh, Gobind Kumar; Jha, Navin; Aryal, Narayan Prasad (International Journal of Atharva, 2025)
In an increasingly complex and interconnected work environment, emotional intelligence (EI) has gained prominence as a vital factor influencing leadership effectiveness. While global studies have established a strong link between EI and leadership outcomes, limited empirical research exists within the Nepalese context, particularly in the commercial banking sector. This study aims to examine the impact of three core dimensions of emotional intelligence viz. self-management (SM) relationship management (RM), and self-awareness (SA) on leadership effectiveness (LE) among employees of commercial banks in Kathmandu, Nepal. A causal research design was adopted, utilizing 197 valid responses from 250 structured questionnaires distributed to banking professionals. Data were analyzed using descriptive statistics, correlation analysis, and multiple linear regression.  The findings revealed that self-awareness emerged as the most significant predictor of leadership effectiveness, followed by relationship management. The findings suggest that emotionally intelligent leadership - particularly anchored in self-awareness and relational competence - is essential for effective leadership within Nepal’s commercial banking sector. These insights hold practical implications for leadership development programs, highlighting the need to prioritize self-awareness and relationship-building skills in training initiatives. The study is limited by its sector-specific focus and reliance on a quantitative approach. Future research should incorporate mixed methods to explore the cultural and contextual nuances of EI in leadership. The novelty of this study lies in its contribution to the limited body of empirical research in Nepal, offering valuable insights into the EI dimensions that most significantly influence leadership effectiveness in emerging economies.